2022
DOI: 10.1039/d2fo00811d
|View full text |Cite
|
Sign up to set email alerts
|

Poria cocos water-soluble polysaccharide modulates anxiety-like behavior induced by sleep deprivation by regulating the gut dysbiosis, metabolic disorders and TNF-α/NF-κB signaling pathway

Abstract: Poria cocos has been traditionally used as folk medicine and functional food in China for more than 2000 years. The water-soluble polysaccharide is the main component of P. cocos decoction....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…A recent study revealed that it upregulates brain–gut peptides and improves the gastrointestinal mucosa and immunity, improving the function of dyspepsia. The reason behind its potential pharmacological effect is the presence of terpenoids and polysaccharides that regulate the imbalance in the microbial community to ameliorate depression and anxiety via the TNF-α/NF-κβ signaling pathway [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study revealed that it upregulates brain–gut peptides and improves the gastrointestinal mucosa and immunity, improving the function of dyspepsia. The reason behind its potential pharmacological effect is the presence of terpenoids and polysaccharides that regulate the imbalance in the microbial community to ameliorate depression and anxiety via the TNF-α/NF-κβ signaling pathway [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“… 65 Muribaculaceae was associated with cognitive impairment and depressive mood and participates in the TNF-α/NF-κB signaling pathway. 66 …”
Section: Discussionmentioning
confidence: 99%
“…65 Muribaculaceae was associated with cognitive impairment and depressive mood and participates in the TNF-α/NF-κB signaling pathway. 66 NF-κB and other members of its family are important regulators in the inflammatory process and participate in the inflammatory and stress process of the organisms. 67,68 TLR4, an upstream member of the NF-κB pathway, widely exists…”
mentioning
confidence: 99%
“…The water-soluble polysaccharide from Poria cocos can also regulate the imbalance of intestinal flora [69]. Atractylodes macrocephala polysaccharide (PAMK) can regulate the composition and activity of intestinal flora, promote the growth of bifidobacteria and lactic acid bacteria, promote the generation of bile acid in the body, and regulate energy metabolism [27].…”
Section: Iron Deathmentioning
confidence: 99%